How aging of the labor force affects equilibrium unemployment - Pascal Hetze; Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2005)
This paper argues that aging of the labor force affects job creation and job destruction. To analyze this, we extend a standard model of equilibrium unemployment and search in the labor market by the distinction between age specific separation risks and a productivity differential between young and elderly workers. Based on the theo- retical model, we identify four regimes of changes in the Beveridge Curve and job creation which can occur if the age structure varies. We also present an econometric model to find out which country relates to which regime. According to the estimates we can identify all four cases. For example, Spain and the US may experience positive effects on employment when the labor force grows older. In contrast to this, the unemployment rate in Germany and Japan will rise as a consequence of the increase in the share of elderly workers.
Keywords: J63; J64; J23; J21; J10; 330; Vacancies and Separations; Unemployment; Job Creation; Aging of the Labor Force; Demographic Change